1999
DOI: 10.1021/ma9804186
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bond Interactions between Urethane−Urethane and Urethane−Ester Linkages in a Liquid Crystalline Poly(ester−urethane)

Abstract: Five model compounds (Uu, Us, DPT, DMT, and MB) and two liquid crystalline poly(ester−urethane)s with inherent urethane and internal and external ester groups were prepared to monitor the hydrogen-bond (H-bond) interactions of urethane−urethane and urethane−ester (including internal and external esters). The model compounds were used to evaluate the extinction coefficient ratios between different free and bonded carbonyl absorption modes in the infrared spectra. The results show extinction coefficient ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…The peak of bonded C=O that is relevant to this study has been marked out and identified according to some references. [16,17] The infrared band of free C=O stretching at 1724 cm -1 shifts to that of the bonded one at 1740 cm -1 . As such, the hydrogen bonding in the SMP is apparent.…”
Section: Interactions Between Solution and Polymermentioning
confidence: 99%
“…The peak of bonded C=O that is relevant to this study has been marked out and identified according to some references. [16,17] The infrared band of free C=O stretching at 1724 cm -1 shifts to that of the bonded one at 1740 cm -1 . As such, the hydrogen bonding in the SMP is apparent.…”
Section: Interactions Between Solution and Polymermentioning
confidence: 99%
“…But these bands are still detectable even above 325°C. Another peak that should be noticed is the absorbance at 1534 cm -1 , which is assigned to the C-N stretching and N-H deformation vibrations of the urethane group [8]. As can be seen at 150°C, this peak shifts to lower wave number at 1509 cm -1 , attributed to the N-H deformation of polyamine [5].…”
Section: Thermal Degradation Mechanismmentioning
confidence: 85%
“…Radiation curing technology, mostly UV curing, offers many advantages during the curing process, in relation to the ecology or environment, energy conservation, economics and in the excellent performance of products [2][3][4]. The most commonly used UV-curable formulations involve unsaturated acrylic oligomers, including epoxy acrylates, polyester acrylates, polyether acrylates, urethane acrylates and silicone acrylates [5][6][7][8]. Among the oligomers used for UV-curable coatings, urethane acrylate oligomers offer a wide range of excellent application properties, such as high impact and tensile strength, abrasion resistance and toughness etc.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a shoulder peak centered around 3440 cm −1 for the films CW/WPU became obviously strong, implying that original inter-and intra-molecular hydrogen bonds in the WPU networks were destroyed resulting from the dispersion of chitin whisker within WPU matrix. Furthermore, the band at 2980-2850 cm −1 of films CW/WPU assigned to the stretching of methylene groups of the polyester soft segment became weaker than that of pure film WPU (28)(29)(30). The intensity of the peaks decreased with an increase of CW, and the extent of decrease is related to the blending ratio, also implying that abundant hydroxyl and acetamide groups in chitin whisker facilitate the formation of hydrogen bonding with NCO group in the hard segment of WPU.…”
Section: Crystallization Behavior and Miscibility Of Nanocompositesmentioning
confidence: 93%